Spin and dry / Mohammad Faris Jamsari ...[et al.] - Jamsari, Mohammad Faris; Bahrain, Muhaimin; Mazlan Hanafi, Muhammad Amir Fariduddin; Razman, Muhammad Rafiq (2015)
Our main target market of our product is for public such as swimming pool, gym or fitness centre users so that their clothes can directly fold into a bag or hang in the locker. Our spin dryer is a common household and a public appliance that used for drying all suitable type of clothes. The process of removing water from clothes in spin dryer is more simple and more gentle. Thus, the drying process is more efficient with less time than the manual drying process where hands twisting method is used. Therefore, it will changes of our style of laundry activities which minimize cost, time and energy. Our product, Spin & Dry is the first innovative dry clothes machine and not yet existed in Malaysia's market.